Appropriateness and complications of androgen deprivation therapy for prostate cancer: Can we do better? A retrospective observational analysis from a referral center. Issue 1 (February 2023) - Oderda, Marco; Bertetto, Oscar; Barbera, Giulia; Calleris, Giorgio; Falcone, Marco; Filippini, Claudia; Marquis, Alessandro; Marra, Giancarlo; Montefusco, Gabriele; Peretti, Federica; Gontero, Paolo
Introduction: Androgen deprivation therapy (ADT) is the key of medical treatment for advanced prostate cancer (PCa), especially in elderly patients. However, the adherence of ADT prescription to current guidelines is not optimal and must be balanced against possible side effects. Aim of this study was to evaluate the prescriptive appropriateness of ADT and ADT-related adverse events in a referral center for PCa. Methods: Five hundred fifty six patients who received an outpatient prescription for ADT from 2014 to 2018 were retrospectively identified from an administrative database. Only standard ADT was considered, including GnRH agonists, GnRH antagonists, and antiandrogens. Prescriptive appropriateness was defined according to the last European Association of Urology (EAU) guidelines. Our cohort was stratified according to age categories and patient follow-up was updated. Results: Four hundred twenty five patients were available for analysis. Mean age was 80 years; 96.3% of our patients fell in the "elderly" category. There was a predominance of GnRH agonists over the antagonists (84.9% vs 13%). 15.5% of ADTs did not have an appropriate indication according to guidelines. Patient compliance to ADT was evaluated as good in 372 (87.5%) cases. ADT-related complications were detected in 166 (39%) patients: bone, cardiovascular, and other complications were reported in 7.3%, 8.9%, and 19% of patients. Progression of disease was noted in 165 (38.8%) cases during ADT. At last follow-up, 124 (30.1%) patients were deceased. Conclusions: In a referral center, most ADT prescriptions followed EAU guidelines, but a non-negligible proportion still did not fall within these indications, exposing patients to unnecessary side effects. Compliance to ADT was generally good with a predominant use of GnRH agonists. Tolerance to ADT was fair, even if standardized reports were lacking.